Metastable 1T′-phase group VIB transition metal dichalcogenide crystals - Lai, Zhuangchai; He, Qiyuan; Tran, Thu Ha; Repaka, D. V. Maheswar; Zhou, Dong-Dong; Sun, Ying; Xi, Shibo; Li, Yongxin; Chaturvedi, Apoorva; Tan, Chaoliang; Chen, Bo; Nam, Gwang-Hyeon; et al. (Nature materials, 2021)
Metastable 1T′-phase transition metal dichalcogenides (1T′-TMDs) with semi-metallic natures have attracted increasing interest owing to their uniquely distorted structures and fascinating phase-dependent physicochemical properties. However, the synthesis of high-quality metastable 1T′-TMD crystals, especially for the group VIB TMDs, remains a challenge. Here, we report a general synthetic method for the large-scale preparation of metastable 1T′-phase group VIB TMDs, including WS 2 , WSe 2 , MoS 2 , MoSe 2 , WS 2 x Se 2(1− x ) and MoS 2 x Se 2(1− x ) . We solve the crystal structures of 1T′-WS 2 , -WSe 2 , -MoS 2 and -MoSe 2 with single-crystal X-ray diffraction. The as-prepared 1T′-WS 2 exhibits thickness-dependent intrinsic superconductivity, showing critical transition temperatures of 8.6 K for the thickness of 90.1 nm and 5.7 K for the single layer, which we attribute to the high intrinsic carrier concentration and the semi-metallic nature of 1T′-WS 2 . This synthesis method will allow a more systematic investigation of the intrinsic properties of metastable TMDs. A general method for the synthesis of high-purity crystals of metastable 1T′-phase transition metal dichalcogenides is reported, providing a source of phase-engineered materials that can be used to systematically explore their intrinsic properties.